An empirical model for analysing and interpreting ventricular measures. Issue 5 (May 1990) - Clark, C; Marbeck, R; Li, D
Abstract : Given the abundant and, at times, contradictory studies of ventricular enlargement in neurological and psychiatric disorders, the current study was carried out to provide an empirical basis for analysing and interpreting these measures. A sample of CT scans on 100 control subject was drawn from the files of the University of British Columbia Department of Radiology and 19 measures of ventricular and head diameter or area were made. The interrelationships of these measures were then examined using factor analytic procedures. Three ventricular dimensions were found. To validate these three dimensions, the relationship of each with age was examined and then the age-corrected scores of seven clinical groups were compared on each of these dimensions. The magnitude of the relationship between these dimensions and age was impressive and each dimension contributed unique information regarding these age-related changes. Moreover, the analysis of the clinical groups suggested that differential patterns of ventricular change were present dependent upon the disease. These results are discussed with a view to integrating the findings of previous studies and planning future studies.